Teaching Practice Patterns in ECE Teacher Program in Distance Education in Indonesia - Sri Tatminingsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2021)
This purpose paper describes a pattern of micro teaching in teacher education through online learning programme using the moodle application. This article was the result of a study with qualitative paradigm. Research method with survey and data collecting using structured interviews and questionnaires. The research subjects were students who took online tutorial in Strengthening Teaching Courses (STC) in The Early Childhood Teacher Education in Universitas Terbuka (UT), Indonesia in 2018. The finding of the research are online micro teaching patterns in the Online STC that have similarities with face-to-face tutorials. Teaching practices should be a cycle: planning, implementation, evaluation and reflection on their own teaching practices. In addition, to evaluate themselves, students can also be evaluated by the others students and peers by online. In online tutorial, the pattern of micro teaching developed is simpler to understand by students independently and can be an alternative practice teaching course in online teacher education program